2005
DOI: 10.2514/1.2165
|View full text |Cite
|
Sign up to set email alerts
|

Practical Design and Flight Test of a Yo-Yo Wire Boom Deployment System

Abstract: A yo-yo-type wire-boom deployment system has been developed and flight tested on a sounding rocket mission. The goal of the work has been to validate a new mechanism that rapidly deploys wire booms from a spinning spacecraft. This work takes a theoretical system design and implements it in practical hardware. The limitations inherent in practical hardware necessitated new theoretical developments. A modified stability analysis has been developed for the case of nonzero axial separation between the wire-boom ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As the wire booms unwrap, the differential can rotation with respect to the subpayload body is controlled via a feedback loop controlling a damping system so that the correct amount of energy is extracted from the system to enable the booms to be radial without rewrapping. This entire operation to deploy the 6‐m tip‐to‐tip booms takes about 8 s. Details on this system's development can be found in the work of Psiaki et al [2000], and the details specific to the SIERRA design can be found in the work of Psiaki et al [2005]. The subpayloads, having a smaller payload body and smaller wires, measure less noise and see smaller shadowing effects than the MAIN payload.…”
Section: Sierra Sounding Rocketmentioning
confidence: 99%
“…As the wire booms unwrap, the differential can rotation with respect to the subpayload body is controlled via a feedback loop controlling a damping system so that the correct amount of energy is extracted from the system to enable the booms to be radial without rewrapping. This entire operation to deploy the 6‐m tip‐to‐tip booms takes about 8 s. Details on this system's development can be found in the work of Psiaki et al [2000], and the details specific to the SIERRA design can be found in the work of Psiaki et al [2005]. The subpayloads, having a smaller payload body and smaller wires, measure less noise and see smaller shadowing effects than the MAIN payload.…”
Section: Sierra Sounding Rocketmentioning
confidence: 99%
“…This is a good approximation for the SIERRA subpayloads. [2][3][4] Hence, the physical wire booms which are flexible all along their length are modeled as simple pendulums for purposes of simulation and estimation. In this work, both the physical booms and their model are described as flexible because their positions can deform with respect to spacecraft coordinates.…”
Section: Flexible-body Model and Simplifying Assumptionsmentioning
confidence: 99%
“…Due to the short duration of the flight, the unstable mode and consequent slow growth of the nutation angle were considered acceptable. 3 The rate of growth of the unstable mode and the decay time constants of the stable modes are functions of the energy dissipated by bending in the booms. A lumped dissipation parameter was calculated for the SIERRA subpayloads in pre-and post-launch empirical studies, predicting stable mode time constants of less than 300 seconds.…”
Section: Flexible-body Model and Simplifying Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations